Lithium ion battery fire extinguishing agent and preparation process

By combining biomass-based materials with nano-silicon dioxide, lithium-ion battery fire extinguishing agents with high mechanical strength and thermal stability are prepared, solving the problems of high cost, high brittleness and insufficient stability in the prior art, and achieving rapid fire extinguishing and no conductive residues.

CN120420635AActive Publication Date: 2025-08-05GUOFU TECH (CHENGDU) GRP CO LTD

Patent Information

Application Number
CN202510480819.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-04-17
Publication Date
2025-08-05
Estimated Expiration
2045-04-17

AI Technical Summary

Technical Problem

Existing lithium-ion battery fire extinguishing agents have problems such as high cost, high brittleness and insufficient stability, making it difficult to effectively extinguish fires at high temperatures and may cause battery short circuits and corrosion.

Method used

Using chitin powder, povidone, ethyl orthosilicate, modified silica soil, glutaraldehyde solution and sodium bicarbonate, biomass pretreatment, cellulose modification, introduction of nanosilicon dioxide and cross-linking drying steps, an aerogel with an interpenetrating network structure is formed, combined with rhamnosuccin and lanolin modification, a three-dimensional network structure is formed to improve mechanical strength and thermal stability.

Benefits of technology

The prepared lithium-ion battery fire extinguishing agent keeps the structure intact at high temperatures, extinguishes fire quickly without conductivity, has good adsorption and cooling effect, and is suitable for industrial needs.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120420635A_ABST
    Figure CN120420635A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of lithium ion battery fire extinguishing agents, in particular to a lithium ion battery fire extinguishing agent and a preparation process. The preparation process comprises the following steps: S1, biomass pretreatment: mixing 40-50 parts of chitin powder with a 2wt% sodium hydroxide solution according to a mass volume ratio of 1: 10, stirring at 60 DEG C for 1-2 hours, and centrifuging and freeze-drying to obtain a chitin crude product; dispersing the chitin crude product in deionized water, and carrying out ultrasonic treatment to obtain a cellulose suspension with the solid content of 1%; s2, cellulose modification: adding 15-20 parts of povidone into the cellulose suspension, and mixing and stirring at 60 DEG C for 1 hour to obtain a modified cellulose suspension; s3, introducing nano silicon dioxide; s4, preparing modified gel; and S5, cross-linking and drying.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of lithium-ion battery fire extinguishing agents, and in particular to a lithium-ion battery fire extinguishing agent and a preparation process thereof. Background Art

[0002] Types of lithium-ion battery fire extinguishing agents include dry powder, gas (such as perfluorohexanone, heptafluoropropane), water-based, aerogel, etc. Among them, the cost of gas fire extinguishing agents is relatively high. Although dry powder fire extinguishing agents have a wide range of applications and are easy to operate, the powder residue is difficult to clean. Water-based fire extinguishing agents have a significant cooling effect, but they are highly conductive and have the risk of causing battery short circuits and corrosion. Therefore, it is very necessary to develop new fire extinguishing agents that are both highly efficient in extinguishing fires, suppressing re-ignition, and protecting equipment.

[0003] In related technologies, aerogel fire extinguishing agents are usually able to quickly cool down and isolate the air. They do not have the conductive properties of water-based fire extinguishing agents. They are relatively environmentally friendly and safe, and are suitable for precision equipment and live scenes. Aerogel fire extinguishing agents usually use inorganic or organic nanomaterials as a skeleton, combined with functional flame retardant ingredients, mainly including mainstream technologies such as silica-based aerogel and graphene aerogel. However, on the one hand, the cost of its raw materials (such as graphene) is relatively high, and on the other hand, aerogels are relatively brittle, and lack stability and mechanical strength, making them unsuitable for high-temperature fire extinguishing of lithium batteries. Summary of the Invention

[0004] The present application provides a lithium-ion battery fire extinguishing agent and a preparation process to solve the problems mentioned in the background technology.

[0005] In a first aspect, a lithium-ion battery fire extinguishing agent is provided, comprising:

[0006] 40-50 parts of chitosan powder, 15-20 parts of polyvidone, 20-25 parts of ethyl orthosilicate, 5-8 parts of 5 wt% rhamnose solution, 4-5 parts of modified attapulgite, 3-5 parts of 25 wt% glutaraldehyde solution, and 5-8 parts of sodium bicarbonate;

[0007] The preparation method of the modified attapulgite comprises the following steps:

[0008] After attapulgite, perfluorohexanone and ammonium alum were mixed in a mass ratio of 2:0.5:0.1, ultrasonic treatment was performed for 10 minutes to obtain modified attapulgite.

[0009] Preferably, the attapulgite particle size is not greater than 5 μm.

[0010] In a second aspect, a method for preparing a lithium-ion battery fire extinguishing agent is provided, wherein the method is used to prepare any of the above lithium-ion battery fire extinguishing agents, and the method comprises the following steps:

[0011] S1. Biomass pretreatment:

[0012] 40-50 parts of chitosan powder and 2 wt% sodium hydroxide solution were mixed in a mass-to-volume ratio of 1:10, stirred at 60°C for 1-2 hours, and centrifuged and freeze-dried to obtain crude chitosan;

[0013] The crude chitosan is dispersed in deionized water, and subjected to ultrasonic treatment to obtain a cellulose suspension having a solid content of 1%;

[0014] S2. Cellulose modification:

[0015] Adding 15 to 20 parts of povidone to the cellulose suspension, mixing and stirring at 60° C. for 1 hour to obtain a modified cellulose suspension;

[0016] S3. Introduction of nano-silicon dioxide:

[0017] 20-25 parts of ethyl orthosilicate are dropped into the modified cellulose suspension, the pH is adjusted to 2-3, 5-8 parts of a 5 wt% rhamnose solution and modified attapulgite with a mass of 10% of the mass of chitin are added, the mixture is stirred in an ice bath at 0-5°C for 2 hours, and then the mixture is heated to 20-25°C for 3 hours to obtain a gel;

[0018] S4. Preparation of modified gel:

[0019] The gel is immersed in an ethanol solution of lanolin, vacuum filtered for 5 to 10 minutes, and then dried at 60° C. for 2 hours to obtain a modified gel, wherein the concentration of the ethanol solution of lanolin is 0.5 to 2 wt %;

[0020] S5, cross-linking drying:

[0021] Adding 3 to 5 parts of a 25 wt% glutaraldehyde solution and 5 to 8 parts of sodium bicarbonate to the modified gel, reacting in a 60° C. water bath for 3 to 4 hours to obtain a wet gel;

[0022] The wet gel is subjected to multiple solvent replacements using an ethanol solution, with a single replacement time of not less than 12 hours, and then subjected to supercritical CO2 drying for 2 to 4 hours to obtain an aerogel. The aerogel is placed in a ball mill and crushed into a powder of 1 to 80 microns to obtain a lithium-ion battery fire extinguishing agent. The drying conditions are 40°C and 10 MPa.

[0023] Preferably, in S2, adding povidone specifically comprises:

[0024] The povidone was dissolved in water at 60° C. and stirred until completely dissolved to obtain a 10 wt % povidone solution. The povidone solution was added to the cellulose suspension to obtain a modified cellulose suspension.

[0025] Preferably, in S3, glacial acetic acid is used to adjust the pH.

[0026] Preferably, in S5, performing multiple solvent replacements on the wet gel using an ethanol solution comprises the following steps:

[0027] The wet gel was placed in a 95% ethanol solution and soaked for 12 hours, and the ethanol solution was replaced and the soaking was repeated 2 to 3 times;

[0028] Soak in anhydrous ethanol for 12 to 24 hours to complete solvent replacement.

[0029] Preferably, in S5, the supercritical CO2 drying conditions are: at room temperature, the temperature is raised to 40°C at a rate of 2-5°C / min, and the pressure is increased to 10 MPa at a rate of 0.5-1 MPa / min.

[0030] In a second aspect, a lithium-ion battery fire extinguishing agent is provided, which is prepared by any of the above methods for preparing a lithium-ion battery fire extinguishing agent.

[0031] The beneficial effects of the technical solution provided by this application include:

[0032] The present application provides a preparation method of a lithium-ion battery fire extinguishing agent, which uses chitosan as a biomass-based material. The chitosan has good adsorption properties while having certain mechanical strength, can adsorb electrolytes, and assist aerogels in isolating oxygen. The chitosan is combined with biomass molecular chains through hydrogen bonds via polyvidone to form an interpenetrating network, thereby improving mechanical strength and inhibiting thermal decomposition. After combining with nano-silica, a hybrid structure is formed, which generates CO2, N2 and a carbon layer after combustion, and sodium bicarbonate decomposes to produce CO2 and Na2O, effectively extinguishing fires without leaving any conductive residue. The rhamnose and lanolin impregnation modification helps to form a three-dimensional network structure of the aerogel, which absorbs heat during decomposition and helps to reduce the temperature. At the same time, it improves the water resistance and thermal stability of the fire extinguishing agent, inhibits combustion, and has a low cost, making it suitable for industrial needs. BRIEF DESCRIPTION OF THE DRAWINGS

[0033] In order to more clearly illustrate the technical solutions in the embodiments of the present application, the following briefly introduces the drawings required for use in the description of the embodiments. Obviously, the drawings described below are only some embodiments of the present application. For ordinary technicians in this field, other drawings can be obtained based on these drawings without any creative work.

[0034] Figure 1 This is a flow chart of the preparation process of the lithium-ion battery fire extinguishing agent provided in this application. DETAILED DESCRIPTION

[0035] To make the purpose, technical solutions, and advantages of the embodiments of this application more clear, the technical solutions in the embodiments of this application will be clearly and completely described below in conjunction with the drawings in the embodiments of this application. Obviously, the described embodiments are part of the embodiments of this application, not all of the embodiments. Based on the embodiments in this application, all other embodiments obtained by ordinary technicians in this field without making creative efforts are within the scope of protection of this application.

[0036] See also Figure 1 As shown, the present application provides a method for preparing a lithium-ion battery fire extinguishing agent, which comprises the following steps:

[0037] S1. Biomass pretreatment:

[0038] 40-50 parts of chitosan powder and 2 wt% sodium hydroxide solution were mixed in a mass-to-volume ratio of 1:10, stirred at 60°C for 1-2 hours, and centrifuged and freeze-dried to obtain crude chitosan;

[0039] The crude chitosan was dispersed in deionized water and subjected to ultrasonic treatment to obtain a cellulose suspension with a solid content of 1%.

[0040] Furthermore, the cellulose suspension is further ultrasonically treated to ensure uniform dispersion.

[0041] S2. Cellulose modification:

[0042] 15 to 20 parts of povidone were added to the cellulose suspension, and the mixture was mixed and stirred at 60° C. for 1 hour to obtain a modified cellulose suspension.

[0043] Specifically, the addition of polyvidone specifically includes:

[0044] Povidone was dissolved in water at 60° C. and stirred until completely dissolved to obtain a 10 wt % povidone solution. The povidone solution was added to the cellulose suspension to obtain a modified cellulose suspension.

[0045] S3. Introduction of nano-silicon dioxide:

[0046] 20-25 parts of ethyl orthosilicate are dropped into the modified cellulose suspension, and after adjusting the pH to 2-3, 5-8 parts of 5 wt% rhamnose solution and modified attapulgite with a mass of 10% of the mass of chitin are added. After stirring in an ice bath at 0-5°C for 2 hours, the mixture is heated to 20-25°C and reacted for 3 hours to obtain a gel.

[0047] The preparation method of modified attapulgite comprises the following steps:

[0048] After attapulgite, perfluorohexanone and ammonium alum are mixed in a mass ratio of 2:0.5:0.1, ultrasonic treatment is performed for 10 minutes to obtain modified attapulgite, wherein the attapulgite has a particle size of no more than 5 μm.

[0049] S4. Preparation of modified gel:

[0050] The gel was immersed in an ethanol solution of lanolin, vacuum filtered for 5 to 10 minutes, and dried at 60°C for 2 hours to obtain a modified gel, wherein the concentration of the ethanol solution of lanolin was 0.5 to 2 wt%.

[0051] S5, cross-linking drying:

[0052] Add 3 to 5 parts of a 25 wt% glutaraldehyde solution and 5 to 8 parts of sodium bicarbonate to the modified gel, and react in a 60° C. water bath for 3 to 4 hours to obtain a wet gel;

[0053] The wet gel is subjected to multiple solvent replacements using an ethanol solution, with a single replacement time of not less than 12 hours, and then subjected to supercritical CO2 drying for 2 to 4 hours to obtain an aerogel. The aerogel is placed in a ball mill and crushed into a powder of 1 to 80 microns to obtain a lithium-ion battery fire extinguishing agent. The specific drying conditions are 40°C and 10MPa.

[0054] Specifically, the wet gel is subjected to multiple solvent replacements using an ethanol solution, comprising the following steps:

[0055] The wet gel was placed in a 95% ethanol solution and soaked for 12 hours, and the ethanol solution was replaced and the soaking was repeated 2 to 3 times;

[0056] Finally, soak in anhydrous ethanol for 12 to 24 hours to complete the solvent replacement.

[0057] Specifically, the supercritical CO2 drying conditions are: at room temperature, the temperature is raised to 40°C at a rate of 2-5°C / min, and the pressure is increased to 10 MPa at a rate of 0.5-1 MPa / min.

[0058] In the following examples and comparative examples, the preparation method of the modified attapulgite used includes the following steps:

[0059] After attapulgite, perfluorohexanone and ammonium alum are mixed in a mass ratio of 2:0.5:0.1, ultrasonic treatment is performed for 10 minutes to obtain modified attapulgite, wherein the attapulgite particle size is not greater than 5 μm.

[0060] Example 1

[0061] The preparation method of the lithium ion battery fire extinguishing agent provided in this embodiment includes:

[0062] S1. Biomass pretreatment:

[0063] 40 g of chitosan powder was mixed with 400 mL of 2 wt% sodium hydroxide solution, stirred at 60° C. for 2 h, and centrifuged and freeze-dried to obtain crude chitosan. The crude chitosan was dispersed in deionized water and ultrasonically treated to obtain a cellulose suspension with a solid content of 1%.

[0064] S2. Cellulose modification:

[0065] 20 g of povidone was dissolved in water at 60° C. and stirred until completely dissolved to obtain a 10 wt % povidone solution. The povidone solution was added to the cellulose suspension prepared in S1 to obtain a modified cellulose suspension.

[0066] S3. Introduction of nano-silicon dioxide:

[0067] 20 g of ethyl orthosilicate was dropped into the modified cellulose suspension, the pH was adjusted to 2 using glacial acetic acid, 5 g of 5 wt% rhamnose solution and 4 g of modified attapulgite were added, and the mixture was stirred in an ice bath at 5°C for 2 h, then heated to 25°C for 3 h to obtain a gel.

[0068] S4. Preparation of modified gel:

[0069] The S3 gel was immersed in a 2 wt% lanolin ethanol solution, vacuum filtered for 5 min, and dried at 60 °C for 2 h to obtain a modified gel;

[0070] S5, cross-linking drying:

[0071] Add 3 g of 25 wt% glutaraldehyde solution and 5 g of sodium bicarbonate to the modified gel of S4, and react in a 60°C water bath for 4 h to obtain a wet gel;

[0072] First, the wet gel was solvent-replaced three times for 12 hours using a 95% ethanol solution, then soaked in anhydrous ethanol for 12 hours, and then dried with supercritical CO2 for 2 hours to obtain an aerogel. The aerogel was placed in a ball mill and crushed into a powder of 1 to 80 microns to obtain a lithium-ion battery fire extinguishing agent. The drying conditions were 40°C and 10 MPa.

[0073] Example 2

[0074] The preparation method of the lithium ion battery fire extinguishing agent provided in this embodiment includes:

[0075] S1. Biomass pretreatment:

[0076] 50 g of chitosan powder was mixed with 500 mL of 2 wt% sodium hydroxide solution, stirred at 60° C. for 1 h, and centrifuged and freeze-dried to obtain crude chitosan. The crude chitosan was dispersed in deionized water and ultrasonically treated to obtain a cellulose suspension with a solid content of 1%.

[0077] S2. Cellulose modification:

[0078] 20 g of povidone was dissolved in water at 60° C. and stirred until completely dissolved to obtain a 10 wt % povidone solution. The povidone solution was added to the cellulose suspension of S1 to obtain a modified cellulose suspension.

[0079] S3. Introduction of nano-silicon dioxide:

[0080] 25 g of ethyl orthosilicate was dropped into the modified cellulose suspension, the pH was adjusted to 3 using glacial acetic acid, 8 g of a 5 wt% rhamnose solution and 5 g of modified attapulgite were added, and the mixture was stirred in an ice bath at 0°C for 2 h, then heated to 20°C for 3 h to obtain a gel.

[0081] S4. Preparation of modified gel:

[0082] The S3 gel was immersed in a 1 wt% lanolin ethanol solution, vacuum filtered for 6 minutes, and dried at 60° C. for 2 hours to obtain a modified gel.

[0083] S5, cross-linking drying:

[0084] Add 5 g of 25 wt% glutaraldehyde solution and 8 g of sodium bicarbonate to the modified gel of S4, and react in a 60°C water bath for 3 h to obtain a wet gel;

[0085] The wet gel was first subjected to two 15-hour solvent replacements using a 95% ethanol solution, then soaked in anhydrous ethanol for 24 hours, and then subjected to supercritical CO2 drying for 4 hours to obtain an aerogel. The aerogel was placed in a ball mill and crushed into a powder of 1 to 80 microns to obtain a lithium-ion battery fire extinguishing agent. The drying conditions were: at room temperature, the temperature was raised to 40°C at a rate of 5°C / min, and the pressure was increased to 10MPa at a rate of 1MPa / min, and the temperature was maintained at 40°C and 10MPa for 4 hours.

[0086] Example 3

[0087] The preparation method of the lithium ion battery fire extinguishing agent provided in this embodiment includes:

[0088] S1. Biomass pretreatment:

[0089] 45 g of chitosan powder was mixed with 450 mL of 2 wt% sodium hydroxide solution, stirred at 60° C. for 2 h, and centrifuged and freeze-dried to obtain crude chitosan. The crude chitosan was dispersed in deionized water and ultrasonically treated to obtain a cellulose suspension with a solid content of 1%.

[0090] S2. Cellulose modification:

[0091] 15 g of povidone was dissolved in water at 60° C. and stirred until completely dissolved to obtain a 10 wt % povidone solution. The povidone solution was added to the cellulose suspension prepared in S1 to obtain a modified cellulose suspension.

[0092] S3. Introduction of nano-silicon dioxide:

[0093] 22 g of ethyl orthosilicate was dropped into the modified cellulose suspension, the pH was adjusted to 2 using glacial acetic acid, 6 g of a 5 wt% rhamnose solution and 4.5 g of modified attapulgite were added, and the mixture was stirred in an ice bath at 2°C for 2 h, then heated to 20°C for 3 h to obtain a gel.

[0094] S4. Preparation of modified gel:

[0095] The S3 gel was immersed in a 0.5 wt% lanolin ethanol solution, vacuum filtered for 10 min, and dried at 60 °C for 2 h to obtain a modified gel;

[0096] S5, cross-linking drying:

[0097] Add 4 g of 25 wt% glutaraldehyde solution and 6 g of sodium bicarbonate to the modified gel of S4, and react in a 60°C water bath for 3 h to obtain a wet gel;

[0098] First, the wet gel was solvent-replaced three times for 12 hours using a 95% ethanol solution, then soaked in anhydrous ethanol for 15 hours, and then supercritical CO2 dried for 2 hours to obtain an aerogel. The aerogel was placed in a ball mill and crushed into a powder of 1 to 80 microns to obtain a lithium-ion battery fire extinguishing agent. The drying conditions were: at room temperature, the temperature was raised to 40°C at a rate of 2°C / min, and the pressure was increased to 10MPa at a rate of 0.8MPa / min, and the aerogel was kept dry at 40°C and 10MPa for 2 hours.

[0099] Example 4

[0100] The preparation method of the lithium ion battery fire extinguishing agent provided in this embodiment includes:

[0101] S1. Biomass pretreatment:

[0102] 45 g of chitosan powder was mixed with 450 mL of 2 wt% sodium hydroxide solution, stirred at 60° C. for 1 h, and centrifuged and freeze-dried to obtain crude chitosan. The crude chitosan was dispersed in deionized water and ultrasonically treated to obtain a cellulose suspension with a solid content of 1%.

[0103] S2. Cellulose modification:

[0104] 18 g of povidone was dissolved in water at 60° C. and stirred until completely dissolved to obtain a 10 wt % povidone solution. The povidone solution was added to the cellulose suspension prepared in S1 to obtain a modified cellulose suspension.

[0105] S3. Introduction of nano-silicon dioxide:

[0106] 25 g of ethyl orthosilicate was dropped into the modified cellulose suspension, the pH was adjusted to 2 using glacial acetic acid, 6 g of a 5 wt% rhamnose solution and 4.5 g of modified attapulgite were added, and the mixture was stirred in an ice bath at 2°C for 2 h, then heated to 25°C for 3 h to obtain a gel.

[0107] S4. Preparation of modified gel:

[0108] The S3 gel was immersed in a 1 wt% lanolin ethanol solution, vacuum filtered for 6 min, and dried at 60 °C for 2 h to obtain a modified gel;

[0109] S5, cross-linking drying:

[0110] Add 4 g of 25 wt% glutaraldehyde solution and 6 g of sodium bicarbonate to the modified gel of S4, and react in a 60°C water bath for 3 h to obtain a wet gel;

[0111] First, the wet gel was solvent-replaced three times for 12 hours using a 95% ethanol solution, then soaked in anhydrous ethanol for 15 hours, and then supercritical CO2 dried for 2 hours to obtain an aerogel. The aerogel was placed in a ball mill and crushed into a powder of 1 to 80 microns to obtain a lithium-ion battery fire extinguishing agent. The drying conditions were: at room temperature, the temperature was raised to 40°C at a rate of 4°C / min, and the pressure was increased to 10MPa at a rate of 0.8MPa / min, and the aerogel was kept dry at 40°C and 10MPa for 2 hours.

[0112] Comparative Example 1

[0113] This comparative example differs from Example 4 in that step S2 is not performed.

[0114] Comparative Example 2

[0115] This comparative example is different from Example 4 in that, in step S2, the amount of polyvidone added is reduced to 5 g.

[0116] Comparative Example 3

[0117] This comparative example differs from Example 4 in that, in step S3, no rhamnose solution is added.

[0118] Comparative Example 4

[0119] This comparative example differs from Example 4 in that step S4 is not performed.

[0120] A 1Ah lithium iron phosphate battery (18650 specification) was used as the test object:

[0121] The fire extinguishing efficiency was tested. The lithium-ion battery fire extinguishing agent prepared in Examples 1 to 4 and Comparative Examples 1 to 4 was loaded into a spray gun with a filling pressure of 1.5 MPa (20°C), a nozzle pressure of 1.2 MPa, and a nozzle outlet diameter of 3 mm. Five lithium batteries were grouped together, fully charged, and placed in a fireproof container. The current and voltage were gradually increased to overcharge the battery. When the battery began to heat up and smoke until an open flame appeared, a small lithium-ion battery fire was successfully triggered. The fire extinguishing agent was sprayed 2 seconds after the flame appeared. The nozzle was 1 m away from the battery surface. A high-speed camera and an infrared thermal imager were used to record the flame and temperature changes after the battery thermal runaway. The time from the occurrence of thermal runaway to the complete extinction of the flame was recorded. The results are shown in Table 1.

[0122] Table 1

[0123] Group Fire extinguishing time (s) Example 1 6.3 Example 2 5.2 Example 3 5.4 Example 4 4.5 Comparative Example 1 6.5 Comparative Example 2 7.6 Comparative Example 3 8.3 Comparative Example 4 8.8

[0124] As can be seen from the table above, the lithium-ion battery fire extinguishing agents prepared in Examples 1-4 all extinguished fires within 7 seconds. This is due to the aerogel's excellent thermal insulation and covering properties, which quickly blocked contact between the battery and oxygen, inhibiting the combustion reaction. No re-ignition occurred within 24 hours. Compared to Comparative Example 4, Example 4 exhibited a faster fire extinguishing time, both due to the lanolin modification imparting a certain degree of flexibility to the aerogel, and the hydrophobic groups in the lanolin reducing the polarity of the fire extinguishing agent.

[0125] Furthermore, mechanical strength was tested. The aerogels prepared in Examples 1-4 and Comparative Examples 1-4 were processed into cylindrical samples with a diameter of 10 mm and a height of 20 mm. The samples were placed between the upper and lower platens of a material testing machine, each coated with silicone oil to prevent adhesion. The samples were then compressed at a compression rate of 0.5 mm / min until the strain reached 50%. The corresponding elastic modulus and compressive strength were obtained based on the stress-strain curve. The results are shown in Table 2.

[0126] Table 2

[0127]

[0128]

[0129] Thermal expansion stress is generated when a lithium battery experiences thermal runaway. A fire extinguishing agent with a certain mechanical strength can maintain structural integrity at high temperatures and continue to function. The aerogels prepared in Examples 1 to 4 have a high elastic modulus and compressive strength, which can ensure that the fire extinguishing agent is not easily destroyed in a lithium battery thermal runaway environment, can withstand a certain high-temperature expansion stress, and maintain its thermal insulation and fire extinguishing properties.

[0130] The anti-caking properties of the lithium-ion battery fire extinguishing agents obtained in Examples 1-4 and Comparative Examples 1-4 were tested with reference to GB 15308-2019. 50g of the lithium-ion battery fire extinguishing agent powder was placed in an aluminum can and stored at 50°C and 75% humidity for 72 hours. The powder was then cooled to room temperature and its surface hardness was tested using a penetrometer. No significant caking occurred in Examples 1-4 or Comparative Examples 1-4.

[0131] The foregoing is merely a list of specific embodiments of the present application, intended to enable those skilled in the art to understand or implement the present application. Various modifications to these embodiments will be readily apparent to those skilled in the art, and the general principles defined herein may be implemented in other embodiments without departing from the spirit or scope of the present application. Therefore, the present application is not limited to the embodiments shown herein, but is intended to conform to the broadest scope consistent with the principles and novel features of the present application.

Claims

1. A lithium-ion battery fire extinguishing agent, characterized in that: It includes: 40-50 parts of chitosan powder, 15-20 parts of polyvidone, 20-25 parts of ethyl orthosilicate, 5-8 parts of 5 wt% rhamnose solution, 4-5 parts of modified attapulgite, 3-5 parts of 25 wt% glutaraldehyde solution, and 5-8 parts of sodium bicarbonate; The preparation method of the modified attapulgite comprises the following steps: After attapulgite, perfluorohexanone and ammonium alum were mixed in a mass ratio of 2:0.5:0.1, ultrasonic treatment was performed for 10 minutes to obtain modified attapulgite.

2. The lithium-ion battery fire extinguishing agent according to claim 1, wherein: The attapulgite particle size is not greater than 5 μm.

3. A method for preparing a lithium-ion battery fire extinguishing agent, characterized in that: It is used to prepare the lithium-ion battery fire extinguishing agent according to any one of claims 1 to 2, and the preparation method comprises the following steps: S1. Biomass pretreatment: 40-50 parts of chitosan powder and 2 wt% sodium hydroxide solution were mixed in a mass-to-volume ratio of 1:10, stirred at 60°C for 1-2 hours, and centrifuged and freeze-dried to obtain crude chitosan; The crude chitosan is dispersed in deionized water, and subjected to ultrasonic treatment to obtain a cellulose suspension having a solid content of 1%; S2. Cellulose modification: Adding 15 to 20 parts of povidone to the cellulose suspension, mixing and stirring at 60° C. for 1 hour to obtain a modified cellulose suspension; S3. Introduction of nano-silicon dioxide: 20-25 parts of ethyl orthosilicate are dropped into the modified cellulose suspension, the pH is adjusted to 2-3, 5-8 parts of a 5 wt% rhamnose solution and modified attapulgite with a mass of 10% of the mass of chitin are added, the mixture is stirred in an ice bath at 0-5°C for 2 hours, and then the mixture is heated to 20-25°C for 3 hours to obtain a gel; S4. Preparation of modified gel: The gel is immersed in an ethanol solution of lanolin, vacuum filtered for 5 to 10 minutes, and then dried at 60° C. for 2 hours to obtain a modified gel, wherein the concentration of the ethanol solution of lanolin is 0.5 to 2 wt %; S5, cross-linking drying: Adding 3 to 5 parts of a 25 wt% glutaraldehyde solution and 5 to 8 parts of sodium bicarbonate to the modified gel, reacting in a 60° C. water bath for 3 to 4 hours to obtain a wet gel; The wet gel is subjected to multiple solvent replacements using an ethanol solution, with a single replacement time of not less than 12 hours, and then subjected to supercritical CO2 drying for 2 to 4 hours to obtain an aerogel. The aerogel is placed in a ball mill and crushed into a powder of 1 to 80 microns to obtain a lithium-ion battery fire extinguishing agent. The drying conditions are 40°C and 10 MPa.

4. The method for preparing a lithium ion battery fire extinguishing agent according to claim 3, wherein: In said S2, adding povidone specifically comprises: The povidone was dissolved in water at 60° C. and stirred until completely dissolved to obtain a 10 wt % povidone solution. The povidone solution was added to the cellulose suspension to obtain a modified cellulose suspension.

5. The method for preparing a lithium ion battery fire extinguishing agent according to claim 3, wherein: In S3, glacial acetic acid is used to adjust the pH.

6. The method for preparing a lithium ion battery fire extinguishing agent according to claim 3, wherein: In S5, performing multiple solvent replacements on the wet gel using an ethanol solution comprises the following steps: The wet gel was placed in a 95% ethanol solution and soaked for 12 hours, and the ethanol solution was replaced and the soaking was repeated 2 to 3 times; Soak in anhydrous ethanol for 12 to 24 hours to complete solvent replacement.

7. The method for preparing a lithium ion battery fire extinguishing agent according to claim 3, wherein: In the above-mentioned S5, the supercritical CO2 drying conditions are: at room temperature, the temperature is raised to 40°C at a rate of 2-5°C / min, and the pressure is increased to 10 MPa at a rate of 0.5-1 MPa / min.

Citation Information

Patent Citations

  • Multi-functional foam extinguishing agent and method for preparing the same

    CN101134130A

  • Macromolecular gel extinguishant

    CN106178375A

  • Preparation method of gel dry water fire extinguishing agent

    CN111054008A

  • Lithium ion battery water-based fire extinguishing agent and preparation process

    CN119185881A

  • Chemical coolant for aerosol fire extinguishing agent and preparation method

    WO2024234427A1

Cited By

  • High-insulation low-hygroscopicity condensed aerosol fire extinguishing agent and preparation method thereof

    CN122075990A

  • High-insulation low-hygroscopic thermal aerosol fire extinguishing agent and preparation method thereof

    CN122075990B